Corporate social responsibility (CSR) and sustainable development during the Covid-19 pandemic - Kubiczek, Jakub; Hadasik, Bartłomiej (Wydawnictwo Uniwersytetu Rzeszowskiego, 2022)
The coronavirus pandemic affected all areas of social life and changed the conditions in which most industries operate. The current forms of profitable business activities were suspended in many sectors of the market, which forced entrepreneurs to adapt to the new market conditions. During the Covid-19 pandemic, particular attention should be paid to the activities of enterprises in two so far closely related areas: corporate social responsibility (CSR) and sustainable development (SD). Enterprises typically pursued sustainable development goals (SDGs) and supported them as part of their CSR. The paper is exploratory in nature and it aims to determine the degree of CSR commitment and the implementation of the SDGs during the first year of the Covid-19 pandemic. The results show that the sudden outbreak of the pandemic and the equally dynamic response of governments left some enterprises in uncertainty as going concerns. However, financially sound companies have become committed to helping the population groups most affected by the Covid-19 pandemic. Moreover, the pandemic situation has significantly distanced companies from achieving the intended long-term Global Goals, and the spread of the Covid-19 disease has a significant (mostly negative) impact on the sustainable development of the world. Furthermore, it is impossible to determine the long-term impact of a pandemic on CSR activities and on the implementation of the SDGs.

Pandemia koronawirusa wpłynęła na wszystkie dziedziny życia społecznego, a także zmieniła uwarunkowania funkcjonowania większości branż. Przynosząca zyski dotychczasowa forma działalności została w wielu gałęziach gospodarki wstrzymana, co wymusiło na przedsiębiorcach dostosowania do nowych uwarunkowań rynkowych. Podczas pandemii Covid-19 szczególną uwagę należy zwrócić na działalność przedsiębiorstw w dwóch do tej pory ściśle ze sobą powiązanych obszarach: społeczna odpowiedzialność biznesu oraz zrównoważony rozwój. Przedsiębiorstwa zazwyczaj realizowały cele zrównoważonego rozwoju oraz wspierały je w ramach społecznej odpowiedzialności biznesu. Artykuł ma charakter przeglądowy, a jego celem jest określenie stopnia zaangażowania przedsiębiorstw w społeczną odpowiedzialność biznesu oraz realizacje celów zrównoważonego rozwoju podczas pierwszego roku trwania pandemii Covid-19. Wyniki pokazują, że gwałtowny wybuch pandemii i równie dynamiczna reakcja rządów spowodowały, że część przedsiębiorstw znalazło się w niepewności kontynuacji działalności. Jednak przedsiębiorstwa o stabilnej sytuacji finansowej zaangażowały się w pomoc najbardziej dotkniętym przez pandemię Covid-19 grupom społecznym. Co więcej, pandemia znacząco oddaliła przedsiębiorstwa od realizacji zamierzonych długoterminowych Globalnych Celów, a rozprzestrzeniająca się choroba Covid-19 istotnie wpływa (w największej mierze negatywnie) na zrównoważony rozwój świata. Ponadto, niemożliwe jest długookresowe określenie wpływu pandemii na działalność z zakresu CSR oraz realizacji celów zrównoważonego rozwoju.
Keywords: corporate social responsibility; CSR; sustainable development; Covid-19; sustainable development goals; społeczna odpowiedzialność biznesu; zrównoważony rozwój; cele zrównoważonego rozwoju